2010
DOI: 10.1007/s10495-010-0473-0
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial KATP channels-derived reactive oxygen species activate pro-survival pathway in pravastatin-induced cardioprotection

Abstract: Reactive oxygen species (ROS) are important intracellular signaling molecules and are implicated in cardioprotective pathways including ischemic preconditioning. Statins have been shown to have cardioprotective effects against ischemia/reperfusion injury, however, the precise mechanisms remain to be elucidated. We hypothesized that ROS-mediated signaling cascade may be involved in pravastatin-induced cardioprotection. Cultured rat cardiomyocytes were exposed to H(2)O(2) for 30 min to induce cell injury. Pravas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Using isolated cardiac cells, we also reported that the protection observed is primarily due to a direct effect on the cardiomyocytes and does not necessarily depend on the endothelial effects of CST [36]. Since in multiple models [39,41,42,51,52,56], including isolated cells [48,51,56], an involvement of PI3K/Akt, PKCs, mitoK ATP channel and ROS-signalling have been observed in ischaemic postconditioning, we hypothesized that the CST-induced cardioprotective response in reperfusion may involve potential signalling proteins (e.g. PI3K/Akt and PKCs) and potential downstream targets and mediators (e.g.…”
Section: Introductionmentioning
confidence: 78%
“…Using isolated cardiac cells, we also reported that the protection observed is primarily due to a direct effect on the cardiomyocytes and does not necessarily depend on the endothelial effects of CST [36]. Since in multiple models [39,41,42,51,52,56], including isolated cells [48,51,56], an involvement of PI3K/Akt, PKCs, mitoK ATP channel and ROS-signalling have been observed in ischaemic postconditioning, we hypothesized that the CST-induced cardioprotective response in reperfusion may involve potential signalling proteins (e.g. PI3K/Akt and PKCs) and potential downstream targets and mediators (e.g.…”
Section: Introductionmentioning
confidence: 78%
“…The effects of statins on cardiac mitochondria are unclear. Pravastatin was shown to mediate cardioprotection through mitochondrial ATP-sensitive potassium (mitoK ATP ) channels in a Langendorff model where the drug was infused 10 min before global no-flow ischemia (55). Opening of mitoK ATP channels is known to cause mild mitochondrial depolarization; we previously showed that depolarization mediated by the uncoupler carbonyl cyanide 4-(trifluoromethoxy) phenylhydrazone (FCCP) was sufficient to trigger Parkin translocation and mitophagy (18).…”
Section: Discussionmentioning
confidence: 99%
“…Increased production of mitochondrial reactive oxygen species (mtROS), altered mitochondrial membrane potential and decreased intracellular ATP levels have been observed with concentrations of statin as low as 1 mM. [68][69][70][71][72] Statins have also been shown to promote a modest increase in cellular ROS and an increase of ATP release in THP-1 monocytes. 56 Statininduced IL-1b production was also shown to be dependent on P2X purinoceptor 7 (P2X7) activation.…”
Section: Future Directions: Upstream Of the Inflammasomementioning
confidence: 99%